IMPLEMENTASI RANGE OF MOTION (ROM) UNTUK MENINGKATKAN KEKUATAN OTOT PADA PASIEN STROKE DI RS ISLAM MALAHAYATI MEDAN - Septi Sarah; Mona Hastuti (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Stroke is a blood circulation disorder in the brain or blockage of blood in the brain which causes disruption of the nervous function of the brain and usually occurs suddenly. Nervous system disorders that occur in stroke sufferers can cause specific symptoms, such as: paralysis of the limbs, problems when speaking including slurred speech, imbalance, changes in consciousness, and even vision problems. The aim of this research is how nursing care is provided for ischemic stroke patients at RSI Malahayati Medan. The research method was carried out at RSI Malahayati Medan in April 2024 with a population of 1 person and the sample in this study was 1 person suffering from SNH (Non-Hemorrhagic Stroke). The results of this research are the evaluation and results of implementation of Mr. T who survived 3 days from the first day to the last day, showing significant changes. On the first day, his muscle strength, three prone to movement, 2 physical weakness, worsened, on the second day, muscle strength, 3, prone to movement, 3 weakness. Physically improved, on the third day muscle strength, 5 susceptibility to movement, 5 physical weakness improved. The conclusion of this research is based on the nursing care that was carried out on Mr. T for 3 days, namely 28 April 2024 - 30 April 2024 with a stroke through implementing range of motion ROM to increase muscle strength in stroke patients at the Malahayati Islamic Hospital in Medan.